Designing Moral and Character Education Animation with Frame by Frame Approach - Vladimir Lim; Bayu Syahputra; Tony Wibowo (Universitas Internasional Batam, 2024)
Moral principles and character development play a pivotal role in our daily lives. In light of this, the author has conceptualized a 2D animation within the action genre to effectively communicate these values to the audience. Employing the frame-by-frame technique as the primary foundation for crafting this 2D animation allows for more imaginative and expressive movements, enhancing the characters' expressiveness. Each frame serves as a key element in constructing a compelling narrative, reinforcing the moral values the author seeks to impart. Consequently, the animation serves as both a source of entertainment and a potent medium for delivering moral messages, creating memorable characters for the audience. The research methodology applied in this study follows the MDLC (Multimedia Development Life Cycle), encompassing six stages: concept, design, material gathering, production, testing, and distribution. The culmination of this research is a 2D animated video designed to convey moral values and character development, complemented by a captivating storyline.